Microarrays de ADN en Microbiología - Aguado, Mónica (Revista Complutense de Ciencias Veterinarias, 2007)
During the last years, the development of the sequencing technology and the bioinformatic tools has allowed a great increase in the scientific studies focused on sequencing complete genomes. New tools for the analysis of this high amount of data have been developed in parallel to the genomes sequencing, such as DNA microarray technology. DNA microarrays allow the analysis of DNA homology or gene expression for thousands of genes in a single experiment. Over the past few years, this powerful technology has been used to explore transcriptional profiles and genome differences for a variety of microorganisms. Thanks to the increase in the complete microbial genome sequences, DNA microarrays are becoming a common tool in many areas of microbial research, including physiology, pathogenesis, epidemiology, ecology and phylogeny.